2011
DOI: 10.1097/mat.0b013e31823769d5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Regional Myocardial Perfusion, Metabolism, MVO2, and Edema After Coronary Sinus Machine Perfusion Preservation of Canine Hearts

Abstract: Machine perfusion improves solid organ preservation for transplantation. We have demonstrated that antegrade perfusion preservation of hearts is superior to cold storage but may be limited by aortic valve incompetence. We hypothesized that retrograde perfusion (RP) through the coronary sinus may provide more reliable perfusate delivery to the heart. This study was designed to determine the optimal perfusion parameters and evaluate regional flow after RP of canine hearts. After donor cardiectomy, canine hearts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…We previously reported that antegrade perfused hearts can develop significant myocardial edema when perfused with Celsior over extended storage intervals [20]. Edema seems to develop much sooner in retrograde perfused hearts, likely due to the increased flow rates required to achieve adequate tissue nutrient flow, and unlike in antegrade perfused hearts, this effect seems to be relatively independent of the preservation solution [17]. The present study suggests that development of myocardial edema in perfused hearts seems to be primarily a mechanical rather than an endothelial effect because it resolves over time as the heart resumes contractility; therefore, at the end of the reperfusion period, differences in water content have largely disappeared.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We previously reported that antegrade perfused hearts can develop significant myocardial edema when perfused with Celsior over extended storage intervals [20]. Edema seems to develop much sooner in retrograde perfused hearts, likely due to the increased flow rates required to achieve adequate tissue nutrient flow, and unlike in antegrade perfused hearts, this effect seems to be relatively independent of the preservation solution [17]. The present study suggests that development of myocardial edema in perfused hearts seems to be primarily a mechanical rather than an endothelial effect because it resolves over time as the heart resumes contractility; therefore, at the end of the reperfusion period, differences in water content have largely disappeared.…”
Section: Discussionmentioning
confidence: 90%
“…One concern with retrograde perfusion is decreased perfusion to certain regions of the heart, especially the right ventricle [15,16]. We previously reported some decrease in the perfusion of the right ventricle; however, the implications of this finding on reperfusion graft function have not been completely investigated [17].…”
mentioning
confidence: 98%
“…26 Our prior canine studies also suggest that RV perfusion is reduced with this technique based on microsphere bead entrapment and lactate-to-alanine ratios. 10 We did not measure RV function directly in the current experiments, although clinically, no RP hearts experienced RV dysfunction or required escalation of inotropic support. Central venous pressure was measured in some animals but a meaningful comparison to static storage hearts was not possible because most animals in the static storage groups required an immediate return to CPB after emptying curves were obtained.…”
Section: Discussionmentioning
confidence: 98%
“…Oxygenated UWMPS was continuously perfused for the entire storage interval at a rate of 20 ml/100 g of myocardium/min and a temperature of 51 Ϯ 21C based on prior canine retrograde perfusion data. 10 A small catheter was secured in the aortic root to obtain serial coronary effluent samples for measuring oxygen level, lactate, and pH. Heart weights were obtained at baseline, after storage, and after reperfusion.…”
Section: Donor Protocolmentioning
confidence: 99%
“…9 Alternatively, heart preservation using continuous perfusion can provide the energy required for metabolism during cold ischemic heart preservation, remove the acidic metabolites, and prolong the time of donor heart preservation by 8-10 h. 10,11 However, continuous perfusion has several shortcomings, such as inducing tissue edema, increased vascular edema, and increased endothelial injury, in addition to the requirement of a special perfusion device and large volumes of preservation solution because of the elongated preservation time, 12-14 some of which cannot be overcome even with retrograde perfusion. 15 Therefore, intermittent perfusion at low temperature may be more advantageous than continuous perfusion 16 as it not only provides metabolic substrates and rinses metabolites as with continuous perfusion but also reduces the total volume of perfusion solution required and decreases the myocardial edema and vascular endothelial injury. However, because both continuous perfusion 15 and intermittent perfusion are affected by perfusion pressure, velocity, and time, [17][18][19] further studies are necessary to identify the parameters for optimal myocardial protection to prevent endothelial cell and smooth muscle cell damage, resulting in increased capillary permeability and release of vasoactive substances and subsequent vasospasm, insufficient microvascular perfusion, and cardiac dysfunction soon after transplantation as well as long-term outcomes (e.g., chronic cardiac allograft vasculopathy).…”
mentioning
confidence: 99%